Technology-driven roadmaps for identifying new product/market opportunities: Use of text mining and quality function deployment. Issue 1 (January 2015) - Jin, Gyungmi; Jeong, Yujin; Yoon, Byungun
Highlights Identifying new product/market opportunities. Developing technology-driven roadmaps. Applications of text mining and quality function deployment for roadmapping. Exploring profitable markets and promising product concepts using technology information. Performing a case study of solar lighting devices to illustrate the proposed approach.